Diversity and Abundance of Soil Collembola during GM Rice Overexpressing Cry1B-Cry1Aa Cultivations at Four Confined Field Trials in West Java - Yayuk Rahayuningsih Suhardjono; Amy Estiati; Syamsidah Rahmawati; Satya Nugroho (Tropical Life Sciences Research, 2022)
Collembola (springtails) is an important soil biology indicator to monitor toxicity or ecological disturbances in the ecosystem. The impact of Bacillus thuringiensis (Bt) rice cv Rojolele events expressing Cry1B-Cry1Aa driven by the maize ubiquitin promoter resistant to yellow rice stem borer (YSB, Scirpophaga incertulas Walker) on non-target Collembola community was assessed. The experiment was performed at four locations under confined field trials according to the Indonesia’s environmental safety regulation on genetically engineered crops. Six transgenic rice events were tested with non-transgenic Rojolele and the moderately resistant IR42 rice varieties as controls. The experimental design was randomised block design with three replicates. Collembola were collected from the bunds between plots using pitfall and Berlese funnel traps at seedling, vegetative and generative stages, as well as at harvesting time. The results showed that Collembola abundance and diversity were significantly affected by both experimental sites and observation times. However, no significant differences in Collembola diversity and abundance between Bt rice and non-Bt controls were observed. Thus, we can conclude that the cultivation of the Bt rice cv Rojolele events expressing Cry1B-Cry1Aa protein fusion do not adversely affect biodiversity and abundance of Collembola at the four confined rice fields.